A combined feeding strategy for enhancing mycophenolic acid production by fed-batch fermentation in Penicillium brevicompactum. Issue 3 (March 2015) - Dong, Yuguo; Xu, Rui; Wang, Lihua; Zhang, Jian; Bai, Chaogang; Sun, Aiyou; Wei, Dongzhi
Highlights This study designed a new combined feeding strategy (F-CPM). This study optimized the fermentation process based on the kinetic analysis. Under F-CPM strategy, the maximum MPA production reached a higher level. This high-efficient feeding strategy made the production of MPA more cost-effective.